Assessing the effectiveness of the full outline of unresponsiveness scale and the Glasgow coma scale in patients of traumatic head injury - Ansari, Fahad; Rai, Arvind (International Surgery Journal, 2021)
Background: The Glasgow coma scale (GCS) is the most commonly used scale while the full outline of unresponsiveness (FOUR) score is a new validated coma scale in the evaluation of the level of consciousness in head injury patients. The aim of the study was to compare and assess the effectiveness of the FOUR score and the GCS in patients of traumatic head injury. Methods: This was a prospective observational study conducted in the department of surgery, Gandhi medical college, Bhopal during a 2 year period in which 100 patients of traumatic head injury were evaluated. The FOUR score and GCS score of these patients were assessed on admission and outcome followed for 2 weeks. Results: The mean age group of 100 patients was 25-45 years with 79% male and 21% female patients. The FOUR scale was found to have a marginally higher sensitivity of 65.6% while the GCS had a sensitivity of 64.2%. The FOUR scale however had a higher specificity of 71.5% compared to 66.4% of GCS. The Youden index showed that FOUR scale (46%) has a better prediction for death than GCS (35%). FOUR had a higher accuracy of 75% than GCS with an accuracy of 65%. Conclusions: Both FOUR score and GCS are valuable scales in assessment of traumatic head injury. The FOUR scale however is more accurate than the GCS in predicting outcome of head injury patients.